Investigation of Different Training Methods Integrated into Soccer Training on Body Composition and Athletic Performance - Mustafa TÜRKMEN; Harun Genç; Ali Erdem Ciğerci (Sergii Iermakov, 2022)
Background and Study Aim. The aim of the study is to investigate the effects of 8-week core and plyometric training on body composition and athletic performance in young male soccer players. Material and Methods. 24 young male soccer players participated in the study voluntarily. The subjects were randomly divided into three separate groups: Core training group (CTG), plyometric training group (PTG) and control group (CG). In addition to soccer training two days a week for 8 weeks, the training was applied to the subjects according to the training programs determined. Physical and performance measurements were made 8 weeks before and after the study. Subject's measurements were analyzed in the SPSS 22 program. Results. The largest percentage and significant difference in agility, speed, vertical jump and plyometric jump parameters was obtained in PTG, while the largest percentage and significant difference in horizontal jump parameters was obtained in CTG. While no difference was found in speed and agility performance in CTG; there are significant differences in jump performance but these differences are lower than the other experimental groups in terms of percentage difference. On the other hand in body composition, a significant change was observed only in the height parameter in PTG. Conclusions. If a faster improvement is desired in the determined athletic performance parameters in a period of eight weeks in soccer, it may be recommended to prefer core and plyometric trainings in addition to branch training.   Keywords: Soccer, core, plyometrics, body composition, athletic performance
Keywords: Athlete Monitoring; Biomedical Engineering; Core (optical fiber); FOS: Medical engineering; Body composition; Quantum mechanics; Significant difference; Athletic performance; Engineering; Vertical jump; Soccer; Health Sciences; FOS: Mathematics; Psychology; Orthopedics and Sports Medicine; Epidemiology of Sports-Related Musculoskeletal Injuries; body composition; Jump; LC8-6691; Physics; Statistics; Biomechanical Analysis of Golf Swing Performance; core; Athletic Training; soccer; Special aspects of education; Computer science; Soccer Performance; Physical Conditioning; Athletic training; FOS: Psychology; Physical medicine and rehabilitation; Plyometrics; Physical Sciences; Telecommunications; Medicine; Sports Science and Performance Analysis; Training Load; Core; athletic performance; plyometrics; Physical therapy; Mathematics